PSYCHOLOGICAL MODEL OF CIVIC IDENTITY FORMATION - Petrovska, Inha (Journal of Education Culture and Society, 2021)
Aim. The research aims to present the psychological concept of civic identity formation, namely author’s view on the nature of civic identity, the stages and psychological mechanisms of civic identity formation. Methods. A system of general scientific methods was used: analysis and synthesis of the main provisions of research sources on the study of civic identity as a complex multidimensional personality formation, comprehension of the psychological foundations of civic identity, systematization and generalization of scientific provisions on the stages and mechanisms of identity. Results. It is proposed to consider civic identity as a kind of organizational identity, which is self-determination in the organizational environment of the state, as well as self-identification with the role of a citizen and is the primary psychological regulator of civic behavior. The main stages of civic identity formation are: perceptual-systemic, normative-community and individual-integrational. The main mechanisms of formation of civic identity are: internalization of stereotypes and attitudes of citizenship; imitation of models of civic behavior; individuation of the meanings (sense) of citizenship; exteriorization of stereotypes, attitudes and patterns of civic behavior; implementation of the experience of interaction with the state and fellow citizens; comprehension of one’s own citizenship. Conclusions. Formation of civic identity (civic protoidentity – reproductive civic identity – productive civic identity) is a dynamic process that has staged nature as it involves a series of successive stages, at each of which civic identity undergoes qualitative changes and is formed as an individual’s awareness and reflection of his/her place, role and degree of activity in the system of interaction with other citizens and the state.